Event study combining magnetospheric and ionospheric perspectives of the substorm current wedge modeling. Issue 12 (9th December 2014) - Sergeev, V. A.; Nikolaev, A. V.; Kubyshkina, M. V.; Tsyganenko, N. A.; Singer, H. J.; Rodriguez, J. V.; Angelopoulos, V.; Nakamura, R.; Milan, S. E.; Coxon, J. C.; Anderson, B. J.; Korth, H.
Abstract: Unprecedented spacecraft and instrumental coverage and the isolated nature and distinct step‐like development of a substorm on 17 March 2010 has allowed validation of the two‐loop substorm current wedge model (SCW2L). We find a close spatiotemporal relationship of the SCW with many other essential signatures of substorm activity in the magnetotail and demonstrate its azimuthally localized structure and stepwise expansion in the magnetotail. We confirm that ground SCW diagnostics makes it possible to reconstruct and organize the azimuthal spatiotemporal substorm development pattern with accuracy better than 1 h magnetic local time (MLT) in the case of medium‐scale substorm. The Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE)‐based study of global field‐aligned current distribution indicates that (a) the SCW‐related field‐aligned current system consists of simultaneously activated R1‐ and R2‐type currents, (b) their net currents have a R1‐sense, and (c) locations of net current peaks are consistent with the SCW edge locations inferred from midlatitude variations. Thanks to good azimuthal coverage of four GOES and three Time History of Events and Macroscale Interactions during Substorms spacecraft, we evaluated the intensities of the SCW R1‐ and R2‐like current loops (using the SCW2L model) obtained from combined magnetospheric and ground midlatitude magnetic observations and found the net currents consistent (within a factor of 2) with the AMPERE‐based estimate. We also ran an adaptive magnetospheric model and show that SCW2L model outperforms it in predicting the magnetic configuration changes during substorm dipolarizations. Key Points: Azimuthal SCW dynamics nicely order various substorm signatures in the tail AMPERE confirms quadrupolar FAC source of SCW supporting two‐loop model SCW2L model outperforms other models in describing dipolarized configuration